A theoretical model for predicting mechanical properties of circular concrete-filled steel tube short columns. (November 2022) - Gao, Weiqi; Zhao, Junhai; Fan, Junchao; You, Haoqiang; Wang, Zhou
Abstract: Circular concrete-filled steel tube (CCFST) short columns have superior mechanical properties and broad application prospects. To rapidly predict its mechanical properties, this paper introduced both the similarities and differences of existing models, evaluated the influence of debonding effect and radial stress on CCFST short columns, selected mechanical properties for materials, considered the stress-path dependence of concrete and the strain hardening of steel tubes, and proposed a theoretical model calculated by an incremental-iterative program. Results suggest that ignoring the radial stress and the de-bonding effect has little effect on the mechanical properties of CCFST short columns without local buckling. As the axial strain increases, the influence of the stress-path dependence on the concrete increases. The concrete in CCFST short columns has no stress-path dependence when the confinement factor is greater than 2.5. In the prediction of hoop strains, load components, load-axial strain curves, and axial load capacity, the proposed model is effective and accurate and is superior to the existing models.